Undesirable Postoperative Anesthesia Outcomes at Two National Referral Hospitals: A Cross-Sectional Study in Eritrea - Yonatan Mehari Andemeskel; Traudl Elsholz; Ghidey Gebreyohannes; Eyasu H. Tesfamariam (Anesthesiology Research and Practice)
Background. Postoperative undesirable anesthesia outcomes are common among patients undergoing surgery. They may affect body systems and lead into more serious postoperative problems. This research is conducted in the Eritrean National Referral Hospitals with the aim of assessing the prevalence of undesirable anesthesia outcomes during the postoperative period. Method. A cross-sectional study design was applied on 470 patients who underwent different types of surgeries within a three-month period. Patients were interviewed 24 hours after operation (POD 1) using the Leiden Perioperative care Patient Satisfaction questionnaire (LPPSq). This study reports one component of a large study conducted. The dimension “Discomfort and needs” of the LPPSq was considered, and the measurements of that dimension are presented in this report. Items of the dimension were standardized and measured using a five-point Likert scale from “Not at all” to “Extremely.” Multivariable logistic regression was used to look for the association of the outcomes with the types of surgery and types of anesthesia using SPSS (Version 22). Results. The prevalence were computed in two manners, prevalence of those with ‘at least a little bit’ outcomes, which was computed to see the total occurrence of these outcomes, and prevalence of those having ‘more than moderate’ outcomes to see the severe experience of these outcomes. Prevalence of the predominant undesirable outcome, postoperative pain, for ‘at least a little bit’ and ‘more than moderate’ were 82.6% and 43.6%, respectively. The rest of the postoperative undesirable outcomes were less frequently reported. Conclusion. Postoperative pain was found to be the most prevalent undesirable outcome. Enhancement of proper assessment and management of postoperative pain through the development and implementation of specific pain management modalities is needed.